2018
DOI: 10.1021/acs.langmuir.8b03019
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Amphiphilic Schiff Base and Selectively Turn on Circularly Polarized Luminescence by Al3+

Abstract: We designed glutamide-derived amphiphilic Schiff bases containing three different aldehyde moieties for the fabrication of circularly polarized luminescence (CPL) emitting materials. Upon self-assembly in acetonitrile, Schiff bases featuring 4-(dimethylamino)-2-hydroxylbenzaldehyde and 1-hydroxy-2-naphthaldehyde groups form supramolecular gels with twist and fiber structures, respectively, whereas Schiff bases featuring 2-hydroxy-1-naphthaldehyde groups form precipitation with flake structures. Although emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Moreover, the heterogeneous structure with nanometer size can reduce the charge diffusion length and effectively facilitate the separation process of charge carriers at the interface, which is also confirmed with the steady-state and transient fluorescence spectrum. In view of the above results, the presently prepared new heterojunction materials provide an exploration of new catalyst fields such as water oxidation and self-assembled composites [52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the heterogeneous structure with nanometer size can reduce the charge diffusion length and effectively facilitate the separation process of charge carriers at the interface, which is also confirmed with the steady-state and transient fluorescence spectrum. In view of the above results, the presently prepared new heterojunction materials provide an exploration of new catalyst fields such as water oxidation and self-assembled composites [52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…Contents (at.%) of prepared composites Ag/TiO2/g-C3N4-X (X = 1, 2, 3) from XPS data. C3N4-1 67 53. 3.37 24.43 3.42 1.25 Ag/TiO2/g-C3N4-2 56.69 3.25 22.19 12.95 4.92 Ag/TiO2/g-C3N4-3 40.84 3.06 20.76 25.61 9.73…”
mentioning
confidence: 99%
“…It was well established that the Schiff bases could effectively coordinate with metal ions. We have reported the coordination of amphiphilic Schiff bases with Al 3+ , where the complex was formed by amphiphilic Schiff bases bound to Al 3+ with a 1:1 molar ratio. Herein, the interaction between formed Schiff base and Al 3+ was investigated by absorption spectra and fluorescence spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CPL with opposite handedness was obtained by tuning the nitrogen position and the metal additive. Aluminum ion (Al 3+ , AlCl 3 , ethanol) (Jin Q. et al, 2018) was found to turn-on the CPL of glutamide-derived amphiphilic Schiff base containing a 1-hydroxyl-2-naphthaldehyde group. Inhibition of photon-induced electron transfer (PET) or excited-state induced proton transfer (ESIPT) enhanced the blue emission and specific chirality transfer from the ligand to the chromophore resulted in observable CPL emission (465 nm, |g lum |∼6.21×10 −4 ).…”
Section: Metal Ionsmentioning
confidence: 99%